Sessile solitary osteochondroma at dorsal scapula: a case report - Rengerla, Saikrishna B.; Warade, Nikhil R.; Tiwari, Sonali (International Journal of Research in Orthopaedics, 2022)
Osteochondroma is the most common benign tumor of the bone that occurs predominantly in metaphyseal regions of the long bones but rarely involves flat bones like scapula. However, this is often the most common primary benign bone tumor affecting scapula. These tumors usually occur in the growing age and cease to extend in size after skeletal maturity. Any increase in swelling of an asymptomatic swelling turning symptomatic should raise the suspicion of a malignancy. Here, we presented a case of swelling over the left scapula of a fourteen-year-old boy by his parents since the past three years, which showed no progress since last 1 year but however they presented to the hospital for cosmetic reasons. We performed an open extra periosteal resection of the osteochondroma using modified Judet’s approach after diagnostic workup and ruling out malignancy and confirmation by post operative histopathological study of resected lesion. Patient was able to perform full range of motion at his left shoulder after 1 month. With no evidence of recurrence even after six months of follow-up post operatively.